Meaning of Education and Wellbeing: Understanding and Preventing the Risk of Loss of Meaning in Students - Baatouche, Nadia; de Maricourt, Paul; Bernaud, Jean-Luc (Frontiers in Psychology, 2022)
The phenomenon of malaise is on the rise at universities, reflecting a deteriorating psychological state that is a combination of anxiety and stress factors (Falissard, 2019). This psychological and emotional upheaval within students is indicative of a fundamental existential issue (Bernaud, 2015; Yalom, 2008). In fact, hidden behind the choice of an educational program is the significance given by the student to their life goals. It is this dimension of attributing meaning to one's education and, more broadly, to one's life (the existential dimension) that we have sought to explore (Baatouche, 2020). We hypothesized that a stable investment in one's life goals and a sense of psychological well-being during one's studies could be fostered by reflective work done alongside the educational process. Our research took the form of a mixed methodological approach to the attribution of meaning to education, including an interpretive phenomenological analysis (IPA) and the experimentation of support for the meaning of education. Four dimensions of meaning were found to be observable in varying degrees in all students, each playing a specific role. Moreover, this research has confirmed that the meaning of studies is not to be understood solely in terms of education, but is part of a singular life story. Reflective work, developing meaning, facilitated by others (advisor, teacher, etc.) can help preserve/restore the feeling of well-being. The work presented in this article predates the pandemic, we will not discuss the amplifying effects of this crisis on existential issues, which some recent studies have highlighted (Arnault, 2021).